Internal control mechanism in mitigating fraud risk cases at account representatives at KPP Pratama X - Fitri Zulvina (President University, 2022)
The practice of fraud in the government sector has become a topic of discussion in the Indonesian media. The Directorate General of Taxes as one of the institutions that focuses on the anti-corruption movement has also become a news highlight with the arrest of one of the directors related to fraud. This study aims to identify the internal control mechanism at the KPP Pratama X in mitigating fraud risk. The process of identifying internal control mechanisms is carried out using the concept of Three Lines of Defense. The study was conducted at the position of Account Representative because the position has the potential for a greater risk of fraud compared to other positions at the KPP Pratama X. The research method used is a qualitative descriptive method, which uses the data obtained from reports at the KPP Pratama X and interviews which are then analyzed using qualitative methods. From the field data obtained, it is known that the KPP Pratama X is still not optimal in carrying out internal control mechanisms in mitigating fraud risk. The results of the study are expected to provide input in the development of internal control mechanisms so that fraud risk can be mitigated properly.